Pengaruh Layanan Bimbingan Kelompok Terhadap Pengelolaan Stres Akademik Siswa Pada Penerapan Kurikulum Merdeka di SMA Negeri 1 Belitang III - Risdayati, Ria; Darma Putri, Ramtia; Surtiyoni, Endang (Global Action and Education for Society, 2025)
Academic stress is pressure caused by educational demands or academic demands that cause tension, feelings of discomfort and changes in behavior. This study aims to determine the effect of group guidance services on the management of students’ academic stress in the implementation of the independent curriculum at SMA Negeri 1 Belitang III. The research method used is quantitative, pre-experimental with a one group pretest and posttest design. Sampling using purposive sampling technique of 8 students in class X.4 who have high levels of academic stress. Data were collected using a pretest and posttest questionnaire and observation. Data analysis using the Wilcoxon Sidned Rank Test to determine changes before and after treatment. The results show a Z count value of -2,521 with an Asymp.sig value of 0,012<0,005. So, Ha is accepted and Ho is rejected. This shows that group guidance services are effective in managing students’ academic stress in the implementation of the independent curriculum. This study recommends that group guidance services with group discussion techniques can continue to be developed as part of the guidance and counseling program in schools to help overcome academic stress at SMA Negeri 1 Belitang III.